Standard and magnetically controlled growing rods for the treatment of early onset scoliosis - Helenius Ilkka J (AME Publishing Company, 2022)
Distraction based spinal instrumentation represents the most common and standard surgical technique to correct early onset scoliosis (EOS), i.e., scoliosis which has been diagnosed before the age of 10 years. Surgical treatment of EOS aims at controlling spinal deformity while maintaining spinal growth which is mandatory for the development of normal lung capacity. To achieve these goals the spinal instrumentation needs to be distracted to facilitate spinal growth during treatment. Distraction can be obtained by repeated surgical lengthenings (traditional growing rods, TGRs) or using magnetically controlled growing rods (MCGRs), which can be lengthened using external remote controller on an outpatient basis. The outcomes of TGR instrumentation for EOS are well described with follow-up until skeletal maturity: normal spinal growth can be maintained, 40-50% of the scoliosis can be corrected, but there is an over 50% risk of complications including deep wound infection, rod failure, and instrumentation pull-out. MCGR instrumentation may reduce the risk of wound related complications, provides similar deformity correction, but may not provide as much spinal growth. Metallosis around the instrumentation necessitates MCGR removal and definitive final instrumented fusion at the end of growth friendly management. Even severe EOS can be treated using distraction based spinal instrumentation.